Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jadohealth.2019.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Maternal Factors and Weight Loss Attempts Among Urban Male and Female Adolescents Living in Soweto, Johannesburg, South Africa

Abstract: South Africa is undergoing rapid urban transition favoring ideals of thinness, which increases eating disorders risk for female adolescents, whereas older women continue to uphold corpulence as a female cultural value. This study aimed to assess the potential conflicting relationship between urban male and female adolescents' weight loss attempts (WLA) and maternal body image norms within households. Methods: The study included a longitudinal sample of motheredaughter and mothereson pairs from the Birth to Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…From Cohen et al's [3] analysis of data from the Birth to Twenty Plus cohort study in South Africa, we also observe differing patterns of weight loss attempts by gender and their association with maternal factors. Boys' behavior is highly correlated with their mothers' attempts, but there is no association between girls' and mothers' behaviors.…”
Section: Weight Control and Body Imagesupporting
confidence: 53%
See 2 more Smart Citations
“…From Cohen et al's [3] analysis of data from the Birth to Twenty Plus cohort study in South Africa, we also observe differing patterns of weight loss attempts by gender and their association with maternal factors. Boys' behavior is highly correlated with their mothers' attempts, but there is no association between girls' and mothers' behaviors.…”
Section: Weight Control and Body Imagesupporting
confidence: 53%
“…Three of the manuscriptsdfrom Brazil, South Africa, and the U.S. [1,3,5]dexamine weight control and body image. Studies in these markedly different areas of the world show similar findings: parental perceptions and messages about weight have an impact on weight management and body image.…”
Section: Weight Control and Body Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Though the mechanisms underlying were not elucidated, accumulated evidence has shown that parenting style and practices may contribute to the weak mediation effect of offspring's lifestyle (31,32). And in westernized context, there were differences regarding lifestyle perception and management in teenagers and their parents (33). In addition, adolescents of this age spent most of their time at school, and they were susceptible to the external environment beyond family (34), and the influence of peers become more influential during adolescence while the impact of mothers and other family members was attenuated (35).…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al. [12] found that although the sons of heavier mothers in South Africa were less likely to try to lose weight, there was no association between mothers' body mass index and daughters' weight loss attempts, suggesting a generational shift among women to ideals of thinness. Chae et al.…”
mentioning
confidence: 99%